An estimate of hernia prevalence in Nepal from a countrywide community survey. (January 2015) - Stewart, Barclay T.; Pathak, John; Gupta, Shailvi; Shrestha, Sunil; Groen, Reinou S.; Nwomeh, Benedict C.; Kushner, Adam L.; McIntyre, Thomas
Abstract: Background : Herniorrhaphy is one of the most frequently performed general surgical operations worldwide. However, most low- and middle-income countries (LMICs) are unable to provide this essential surgery to the general public, resulting in considerable morbidity and mortality. This study aimed to estimate the prevalence, barriers to care and disability of untreated hernias in Nepal.Methods : Nepal is a low-income country in South Asia with rugged terrain, infrastructure deficiencies and a severely under-resourced healthcare system resulting in substantial unmet surgical need. A cluster randomized, cross-sectional household survey was performed using the validated Surgeons OverSeas Assessment of Surgical (SOSAS) tool. Fifteen randomized clusters consisting of 30 households with two randomly selected respondents each were sampled to estimate surgical need. The prevalence of and disability from groin hernias and barriers to herniorrhaphy were assessed.Results : The survey sampled 1350 households, totaling 2695 individuals (97% response rate). There were 1434 males (53%) with 1.5% having a mass or swelling in the groin at time of survey (95% CI 1.8–4.0). The age-standardized rate for inguinal hernias in men ranged from 1144 per 100, 000 persons between age 5 and 49 years and 2941 per 100, 000 persons age ≥50 years. Extrapolating nationally, there are nearly 310, 000 individuals with groin masses and 66, 000 males with soft/reducible groin masses in need of evaluation in Nepal. Twenty-nine respondents were not able to have surgery due to lack of surgical services (31%), fear or mistrust of the surgical system (31%) and inability to afford care (21%). Twenty percent were unable to work as previous or perform self-care due to their hernia.Conclusions : Despite the lower than expected prevalence of inguinal hernias, hundreds of thousands of people in Nepal are currently in need of surgical evaluation. Given that essential surgery is a necessary component in health systems, the prevalence of inguinal hernias and the cost-effectiveness of herniorrhaphy, this disease is an important target for LMICs planning surgical capacity improvements. Highlights: Inguinal hernias in Nepal ranged from 1144 per 100, 000 men age 5 and 49 years and 2941 per 100, 000 men age ≥50 years. Though a significant unmet surgical need, hernia rates from other countries, such as Sierra Leone, may be greater. Fear or mistrust was a main reason for not seeking herniorrhaphy; this is an often over-looked barrier to surgical care.